2007
DOI: 10.1038/oby.2007.317
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Decrease of Adipocyte Size after Rosiglitazone Treatment in High‐ and Low‐Fat‐Fed Rats

Abstract: JOHNSON, JULIA A., STEVEN E. TRASINO, ANTHONY W. FERRANTE, JR., AND JOSEPH R. VASSELLI. Prolonged decrease of adipocyte size after rosiglitazone treatment in high-and low-fat-fed rats. Obesity. 2007;15:2653-2663. Objective: The anti-diabetic thiazolidinediones (TZDs) stimulate adipocyte differentiation and decrease mean adipocyte size. However, whether these smaller, more insulinsensitive adipocytes maintain their size after TZD therapy is discontinued has not been studied. Research Methods and Procedures:Adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 51 publications
3
23
0
Order By: Relevance
“…20,21 Epididymal white adipose tissue of both chow and HFD-fed NOX4-deficient mice presented larger adipocytes analyzed either as mean cell size or cell size distribution ( Figures 3a and b). Along with adipose tissue hyperthrophy, molecular signs of enhanced adipocyte differentiation and adipose tissue remodeling/hypertrophy were observed.…”
Section: Resultsmentioning
confidence: 99%
“…20,21 Epididymal white adipose tissue of both chow and HFD-fed NOX4-deficient mice presented larger adipocytes analyzed either as mean cell size or cell size distribution ( Figures 3a and b). Along with adipose tissue hyperthrophy, molecular signs of enhanced adipocyte differentiation and adipose tissue remodeling/hypertrophy were observed.…”
Section: Resultsmentioning
confidence: 99%
“…triggers new LD formation during adipogenesis ( 59 ). However, prolonged treatment is known to be antiobesogenic, to promote lipolysis, and to block LD fusion, resulting adipocytes containing small LDs ( 60,61 ).…”
Section: Comparison Of Lipid-quant With Standard Methodsmentioning
confidence: 99%
“…It has been shown in animal models that rosiglitazone lowers circulating triglyceride and free fatty acids and hence improves insulin sensitivity ( 67,68 ) and reduces adipocyte size and fat accumulation in muscle ( 59,60 ). In cultured human subcutaneous adipocytes and in combination with insulin, rosiglitazone stimulated lipolysis in vitro by guest, on www.jlr.org Downloaded from .html http://www.jlr.org/content/suppl/2015/09/01/jlr.D059758.DC1 Supplemental Material can be found at:…”
Section: D-glucosementioning
confidence: 99%
“…In addition, it was shown that pretreatment with Rosi and other TZDs leads to the reduction of the adipocyte cell size (Johnson et al, 2007;Velebit et al, 2008). This may be due to alterations in membrane dynamics; however, the mechanism of cell size reduction was not studied yet.…”
Section: Rosiglitazone Increases the Plasma Membrane Glut4 Density VImentioning
confidence: 99%